Manfaat Klinis Insulin Glargine U300 - Insulin Basal Generasi Kedua: Analisis - Nanang Miftah (PT Kalbe Farma Tbk., 2024)
Untreated diabetes can lead to complications and increase the risk of death. Many patients with type 2 diabetes will require injectable medication within 5-10 years after diagnosis, following the failure of two or three oral antidiabetic therapies. Adding basal insulin can be well tolerated, more effective with lower risks of hypoglycemia and weight gain compared to other insulin regimens, but it carries a risk of hypoglycemia. Insulin glargine U300, with its special formulation, reduces the risk of hypoglycemia in diabetic patients.